Petrology of the Pan-African high-K alkali-calcic Bocaranga plutonic complex in the Adamawa-Yadé domain (Central African Republic): Nature, origin and contribution to geodynamic reconstruction of the Central African fold belt - Rodrigue Martial Topien; Jules Tcheumenak Kouémo; José Kpéou; Gaetan Moloto-A-Kenguemba; Maurice Kwékam (Solid Earth Sciences)
The Bocaranga plutonic complex belongs to the northwestern extension Adamawa-Yadé Domain of the Central African Fold Belt (CAFB) in the Central African Republic (CAR). Six petrographical units are recorded in the Bocaranga plutonic complex: (i) a coarse-grained biotite granite, (ii) hornblende-biotite granite, (iii) fine-grained biotite granite, and (iv) two micas granite emplaced in Pan-African metamorphic basement rocks composed of (v) gneisses and (vi) amphibolites. Their chemical compositions are similar to quartz monzonites, monzogranite, syenogranite and alkali granite, respectively. The pluton rocks are metaluminous to weakly peraluminous I-type granitoids, hornblende-biotite granite are magnesian and high-K alkaline, while grained biotite granite and fine-grained biotite granite are ferroan, alkalic-calcic and shoshonitic, whereas the two micas granite are weakly to strongly peraluminous and calc-alkaline. The evolution of the major elements (Al2O3 and CaO) and some trace elements (Sr) suggest that fractional crystallization controlled by plagioclase is the main magma differenciation process which influenced the magmatic evolution in this plutonic complex. However, the presence of gneiss xenoliths and mafic enclaves within the plutonic complex, combined to the geochemical data, indicate that the Bocaranga plutonic complex is most likely the result of mixing between mantle- and crust-derived magmas, with high crustal implication for coarse-grained biotite granite, fine-grained biotite granite and two micas granite and high mantle one for hornblende-biotite granite. High U–Th content displays by two-mica granite the high REE content display by all the plutonic rocks indicate that these rocks appear to be respectively favourable for mineralisation in the aforemention elements, thus indicating that the Bocaranga area may represents a potential exploration target for U–Th and REE deposits. The Bocaranga plutonic complex is a synkinematic pluton whose emplacement is synchronuous to the D2 ductile deformation phase related to linear lithospheric delamination along the MBéré Shear Zone around 620-550 Ma during the late-to post-collisional history the Pan-African orogeny. Such granitic plutons are common in the Orogenic Belt of Central Africa and the Brasiliano Belt.